Efficient low-temperature wastewater treatment by Pseudomonas zhanjiangensis sp. nov.: a novel cold-tolerant bacterium isolated from mangrove sediment - Li, Ming; Hu, Xixi; Ni, Tiancheng; Ni, Yuan; Li, Changran; Xue, Dong; Li, Feng (Frontiers in Microbiology, 2024)
A novel heterotrophic, cold-tolerant bacterium, designated Pseudomonas zhanjiangensis 25A3ET, was isolated from mangrove sediment and demonstrated excellent efficiency in cold wastewater treatment. Phylogenetic analysis based on 16S rRNA gene sequences positioned strain 25A3ET within the genus Pseudomonas, showing the highest similarity (98.7%) with Pseudomonas kurunegalensis LMG 32023T. Digital DNA–DNA hybridization (dDDH) and average nucleotide identity (ANI) values were below the species delineation thresholds (70% for dDDH, 95% for ANI), indicating that strain 25A3ET represents a novel species. This strain demonstrated high efficiency in removing nitrogen (N) and organic pollutants under low-temperature conditions. Specifically, it achieved 72.9% removal of chemical oxygen demand (COD), 70.6% removal of ammoniacal nitrogen (NH4+-N), and 69.1% removal of total nitrogen (TN) after 96 h at 10°C. Genomic analysis identified key genes associated with cold adaptation, nitrogen removal and organic matter degradation. These findings indicate that Pseudomonas zhanjiangensis 25A3ET holds significant potential for application in cold temperature wastewater treatment, offering a promising solution for environmental remediation in regions with low ambient temperatures.